Predictors of professional help-seeking for emotional problems in Afghan and Iraqi refugees in Australia: findings from the Building a New Life in Australia Database - Shameran Slewa-Younan; Pilar Rioseco; Maria Gabriela Uribe Guajardo; Jonathan Mond (BMC, 2019)
Abstract Background Refugees are particularly vulnerable to poor mental health outcomes due to exposure to pre migration trauma and post migration stressors. Research has demonstrated evidence to suggest that the professional help-seeking among refugee groups is low or problematic. This study seeks to examine help-seeking for emotional problems in two large samples of Iraqi and Afghan refugees in Australia. Methods This study uses data from two waves of the Building a New Life in Australia, the longitudinal study of Humanitarian migrants. The data was collected face-to-face between 2013 and 2016, among humanitarian migrants. All participants held a permanent protection visa and had arrived in Australia or been granted their visa between period of May to December 2013. The study sample included 1288 participants born in Iraq and Afghanistan (aged 15 and over). In the Wave 3 interview (2015-2016) participants reported on professional help received to deal with emotional problems. Results Approximately 36 and 37% of the Iraqi and Afghan groups respectively, reported seeking help for emotional problems. Within the Iraqi group, associations between mental health status, namely general psychological distress and PTSD and help-seeking were found but this was not present in the Afghan group, where age seemed to play a role in help-seeking. Frequency of help received was low with approximately 47% of the Iraqi and 57% of the Afghan groups reporting having received help 5 times or less in the last 12 months. Conclusions Findings from this study provide clear directions on areas where culturally tailored mental health promotion programs should target in these two refugee communities. Further, the differences in help-seeking behaviour of these communities should be noted by both clinicians and policy makers as efforts to provide culturally responsive mental health services.